Treatment of malignant airway stenosis with extracorporeal membrane oxygenation under low-dose anticoagulation: A case report - Jingsha Zhao; Peng Cui; Ziwei Zhou; Bin Niu; Chuanliang Pan (Heliyon, 2023)
The occurrence of airway obstruction due to severe stenosis from lung cancer poses a significant risk of asphyxia. Although the placement of a metallic stent may relieve the obstruction, the procedure is associated with a high risk of asphyxia. To mitigate this risk, extracorporeal membrane pulmonary oxygenation (ECMO) has been proposed to temporarily substitute for cardiopulmonary function during the procedure. However, the use of systemic anticoagulation with heparin during ECMO may increase the likelihood of bleeding during surgery. This case report describes a successful treatment of a patient with malignant central airway obstruction through low-dose heparin veno-venous ECMO. This approach resulted in reduced intraoperative bleeding and invasive operation time, allowing for prompt postoperative withdrawal and recovery.